Peningkatan Kemampuan Komunikasi Matematika Melalui Strategi Problem Based Learning (PTK Pada Siswa Kelas VIIC Semester Genap SMP Negeri 22 Surakarta Tahun 2013/ 2014) - Hastuti1, Windha Puri, Prof. Dr. Sutama, M.Pd (2015)
Communication skills and critical problem solving in mathematics learning mastered. This is because people need intellectuals who are able to solve problems systematically and able to interpret into oral and written language that is easily understood. PBL learning strategy has the advantage of improving communication skills both in the classroom. This study aims to assess the improvement of mathematical communication skills in students of SMP Negeri 22 Surakarta VII C class second semester of the school year 2013/2014 through strategies Problem Based Learning (PBL). The method used in this research is classroom action research method consists of two cycles, each cycle consisting of five stages, namely the orientation of students on issues, organize the students to learn, guiding the investigation of individuals and groups, to develop and present the results of the work, and to analyze and evaluate the process of problem solving. Data was analyzed using descriptive comparative analysis that compares the ability of communication in the initial conditions, the first cycle and the second cycle. The results showed an increase in students' mathematical communication skills that can be seen from the increase in the indicators include: 1) students are able to communicate verbally before actions 23.52%, 52.94% first cycle, second cycle and 73.52%, 2) students able to communicate in writing before action 26.47%, 58.82% the first cycle, and the cycle II 73.52%, 3) the student is able to communicate the image before actions 29.41%, 52.94% the first cycle, and the cycle II 82.35% 4) the student is able to communicate to explain the concept of prior actions 20.58%, the first cycle of 50%, and 76.47% second cycle. Based on the description above concluded that the implementation strategy Problem Based Learning in mathematics learning can improve students' mathematical communication.